Aspen HYSYS simulation for biodiesel production from waste cooking oil using membrane reactor - Abdurakhman, Y.B. (Institute of Physics Publishing, 2017)
Biodiesel is a promising energy alternative solution to cater the demand of clean sustainable energy sources. Conventional biodiesel production is done by transesterification method using stirred tank reactor and homogeneous base catalyst, then followed by purification process. However, there are some drawbacks associated with this method. They include soap formation, sensitivity to free fatty acid (FFA) content and purification difficulties. Due to these downsides, biodiesel production using heterogeneous acid catalyst in membrane reactor is proposed. This project is aimed to study the effect of FFA content and membrane separation effectiveness on FAME yield. Waste cooking oil, inorganic pressure-driven membrane and WAl is used as raw material, membrane and heterogeneous acid catalyst, respectively. Biodiesel yield formulation is derived from literature data and then used in an Aspen HYSYS process simulation. Early phase cost estimation shows that FFA content does not affect the estimated capital investment, while the membrane separation effectiveness does significantly. Future work will include its comparison with the conventional biodiesel production process. © Published under licence by IOP Publishing Ltd.